If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = (-13) + x 28 = -13 + x Solving 28 = -13 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 28 + -1x = -13 + x + -1x Combine like terms: x + -1x = 0 28 + -1x = -13 + 0 28 + -1x = -13 Add '-28' to each side of the equation. 28 + -28 + -1x = -13 + -28 Combine like terms: 28 + -28 = 0 0 + -1x = -13 + -28 -1x = -13 + -28 Combine like terms: -13 + -28 = -41 -1x = -41 Divide each side by '-1'. x = 41 Simplifying x = 41
| 5/×=1 | | 17=k/2 | | X+-11=7x+-13 | | 3+7n=87-5n | | 8x10/-5 | | 5(a-6)-3=5-(a+2) | | 17=3x+5+4x-9 | | 18=10y-2 | | 0.11-2.2h=9.61+16.1h-17.3h | | 8*10/-5 | | 8=-5/x-8 | | 20a=280 | | (3x-7)(-x^2-4x+5)=0 | | 5=6x+19 | | -6+12=3x-2(x-7) | | 2/3r | | y+7-4(-3y-1)=3(y-1) | | 2x^2-5x^2-12x+30= | | 3xy^2+6y^2+40xy+80y-28x-56=0 | | -5s=5-4s | | 8=5/x-8 | | 6x-12=18x+6-12x | | -154=-5(8+4x)+x | | (6y-7)=-1 | | 8(1/4x-1/4) | | -82=5x-2 | | -6=-n | | 18q-19=12-18+19q | | 2x-6x-6=90 | | -6=n | | 4+4k=-8+k | | -300=-20p |